Salmonella spp. in meat-type quails (Coturnix coturnix coturnix) in the State of São Paulo, Brazil - Freitas Neto, Oliveiro Caetano de [UNESP]; Angela, Henrique Lopes da [UNESP]; Soares, Nilse Maria; Guastalli, E. A. L.; Almeida, Adriana Maria de [UNESP]; Berchieri Junior, Angelo [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2013)
In the present study Salmonella spp. was surveyed in four flocks of meat-type quails reared in a farm that also had processing plant on site, located in the region of Bastos, state of São Paulo, Brazil. Meconium samples of one-day-old quail chicks were collected from transport cardboard boxes. Cecal content was collected on days 7, 14, 21, 28 and 35 of rearing. At 36 days of age, birds were slaughtered in the farm's processing plant, where two samples of water from the scalding and the chilling tanks and four carcasses per flock were collected. All samples were examined for Salmonella spp. using traditional bacteriological methods. Salmonella spp. was present in meconium samples of three flocks and in cecal feces of the four flocks. This bacterium was also isolated in the chiller water and in the carcasses of three of the evaluated flocks and in the scalding water of one flock. In this study, S. enterica subspecies enterica 4, 5, 12; S. Corvalis; S. Give; S. Lexington; S. Minnesota; S. Schwarzengrund; S. Rissen and S. Typhimurium were the eight serovars identified.
Keywords: Carcass; meat-type quails; Salmonella spp.; processing plant